Speed calibration for mobile robot as prototypes to smart vehicles / Zulfikri Paidi ... [et al.] - Paidi, Zulfikri; Muhd Zain, Nurzaid; Othman, Mahfudzah; Mohd Mokhtar, Siti Hajar (UiTM Cawangan Perlis, 2020)
Many studies have been done to find the best formula in building a vehicle with self-driving ability. In order for the vehicle to be smart and able to drive on its own, several factors need to be improved. One of the factors is the ability to make decisions. This research conducted experiments on small-scale mobile robots - also known as robot cars - as prototypes to smart vehicles to find the appropriate value for the driving speed of the vehicle after calibration. The study was conducted using Arduino board hardware, remote robot cars, remote controls for remote robot cars, and rotary encoders. Three main experiments were completed to test the calibrated speed values, namely first test on straight line, test on corner lane, and last test on combination of straight path & corner lane. Simulations for road routes are also made using cardboard, sandpaper and carpet. The results of experimental analysis found that as the speed of a robot car increases, the longer it takes to make a single wheel rotation.